Wordsworth and the enlightenment idea of pleasure - Boyson, Rowan (Cambridge studies in romanticism, 2012)
"Ancient questions about the causes and nature of pleasure were revived in the eighteenth century with a new consideration of its ethical and political significance. Rowan Boyson reminds us that philosophers of the Enlightenment, unlike modern thinkers, often represented pleasure as shared rather than selfish, and she focuses particularly on this approach to the philosophy and theory of pleasure. Through close reading of Enlightenment and Romantic texts, in particular the poetry and prose of William Wordsworth, Boyson elaborates on this central theme. Covering a wide range of texts by philosophers, theorists and creative writers from over the centuries, she presents a strong defence of the Enlightenment ideal of pleasure, drawing out its rich political, as well as intellectual and aesthetic, implications"--